Hempcrete - modern solutions for green buildings. Issue 1 (1st April 2022) - Lupu, M L; Isopescu, D N; Baciu, I-R; Maxineasa, S G; Pruna, L; Gheorghiu, R
Abstract: It is widely established that the building industry has a negative impact on the environment and a significant influence on the phenomena that contribute to climate change. Traditional construction materials, such as cement, contribute considerably to environmental pollution. Given the enormous quantity of energy and materials used by the construction sector, this industry must adopt more sustainable practices. Nowadays, an increasing number of natural building materials are used in the structural component or the insulation of buildings. As a result, natural construction materials may be a superior alternative to accomplish this goal. This article discusses the features and applications of hempcrete in the building industry. Hempcrete is a sustainable material composed of industrial hemp, lime as a binder, and water. Due to hemp's porous structure, it has deformation capacity, sound-absorbing qualities, better hygrothermal properties than conventional concrete, and, depending on the proportions of hemp, lime, and water, fire resistant capabilities due to the presence of lime.